2011
DOI: 10.1039/c1cc13416g
|View full text |Cite
|
Sign up to set email alerts
|

Hot-injection synthesis of iron/iron oxide core/shell nanoparticles for T2 contrast enhancement in magnetic resonance imaging

Abstract: Here we report a new, bench-top synthesis for iron/iron oxide core/shell nanoparticles via the thermal decomposition of Fe(η(5)-C(6)H(3)Me(4))(2). The iron/iron oxide core/shell nanoparticles are superparamagnetic at room temperature and show improved negative contrast in T(2)-weighted MR imaging compared to pure iron oxides nanoparticles, and have a transverse relaxivity (r(2)) of 332 mM(-1) s(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 29 publications
2
38
0
1
Order By: Relevance
“…32,33 The oxide layer consists of Fe 3 O 4 (magnetite) or c-Fe 2 O 3 (maghemite) or a combination of both. For body centered cubic (bcc) structured Fe, particles tend to adopt a faceted shape (as it is shown in Figures 1(f) and 1(h) for particles larger than $15 nm).…”
Section: Resultsmentioning
confidence: 99%
“…32,33 The oxide layer consists of Fe 3 O 4 (magnetite) or c-Fe 2 O 3 (maghemite) or a combination of both. For body centered cubic (bcc) structured Fe, particles tend to adopt a faceted shape (as it is shown in Figures 1(f) and 1(h) for particles larger than $15 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Shavel et al [6] and Mahmoud et al [7] synthesized iron/iron oxide nanocubes using thermal decomposition and chemical reduction methods, respectively. Herman et al [8] and Cheong et al [9] also succeeded to synthesize iron/iron oxide core/shell nanoparticles using thermal decomposition method while changing the surfactant and precursors. More recently, Lixia et al [10] and Hongwang et al [11] also synthesized α-Fe/Fe 3 O 4 nanocomposites with lamellar structure using hydrothermal method.…”
Section: Introductionmentioning
confidence: 95%
“…This substance includes a large value of for the iron core and biocompatibility of the iron oxide shell. Previous studies indicated that the nanoparticles with this type of structure possess a saturation magnetization 4 of 12 kG at 14 nm [20] and 16 kG at 40 nm [21], which is twice that of iron oxide. Little is, however, known as to their long-term durability.…”
Section: Alternative Strategiesmentioning
confidence: 99%